(untitled) (Педагогіка вищої та середньої школи, 2022)
It has been considered that there are some effective ways of professional training o f students on speciality Yeography on the basis o f determining o f four (4) levels in mastering knowledge as their ability to accomplish the system o f actions as for soloing pedagogical tasks.